Pengaruh Program Pemutihan Pajak, Penerapan E-Samsat dan Kesadaran Wajib Pajak terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor (Studi Pada Kantor Samsat Kab. Bandung II Soreang Periode 2019-2023) - Ahmad, Huwan Wan Nur; Devyanthi, Devyanthi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
PThis research aims to analyze the influence of the Tax Whitening Program, Implementation of E-Samsat, and Taxpayer Awareness on Motor Vehicle Taxpayer Compliance at the Bandung II Soreang Regency Samsat Office for the 2019–2023 period. This research used a quantitative approach with a purposive sampling method, and primary data was obtained through questionnaires distributed to 100 respondents. Data analysis was carried out using the SPSS version 27 application. The research results showed that the Implementation of E-Samsat and Taxpayer Awareness had a positive and significant effect on Taxpayer Compliance, while the Tax Whitening Program had no effect on Taxpayer Compliance.